2015
DOI: 10.1109/jphot.2015.2416122
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Ultraflat Near-Infrared Supercontinuum Generation Pumped by a Continuous Amplified Spontaneous Emission Source

Abstract: A high-power ultraflat near-infrared supercontinuum (SC) is generated in a section of photonic crystal fiber (PCF) pumped by an amplified spontaneous emission (ASE) source instead of continuous-wave (CW) and pulsed lasers. A low-power ASE seed at 1 m is amplified to be 90.9 W by two fiber amplifiers and then emitted from a 10-m-core fiber. Using this ASE source to pump a section of 100-m-long PCF, a 49.5-W near-infrared SC is obtained, and the 5-dB spectral bandwidth is 760 nm, covering from 1062 to 1822 nm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Such kind of light sources are successful in many applications, including high-precision fiber-optic gyroscopes [1,2], low-coherence interferometry [3], optical coherence tomography [4,5], etc. Recently, it was demonstrated that nanosecond ASE pulses produced by actively Q-switched fiber lasers may provide an effective pump for supercontinuum generation [6][7][8][9]. ASE sources may also serve as seed for CW amplifying to a multi-hundred watts level with inherently suppressed SBS because of the broad ASE spectrum [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Such kind of light sources are successful in many applications, including high-precision fiber-optic gyroscopes [1,2], low-coherence interferometry [3], optical coherence tomography [4,5], etc. Recently, it was demonstrated that nanosecond ASE pulses produced by actively Q-switched fiber lasers may provide an effective pump for supercontinuum generation [6][7][8][9]. ASE sources may also serve as seed for CW amplifying to a multi-hundred watts level with inherently suppressed SBS because of the broad ASE spectrum [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the utilizations of high power SFSs in many fields, such as mid-infrared laser and supercontinuum generation [10,11] , random fiber laser, and Raman fiber laser pumping [12][13][14] and spectral beam combination [15] , have been demonstrated in recent years for its inherent unique incoherence and high temporal stability characteristics. Consequently, the performance scalability of high power SFS is extremely significant.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al achieved 1.01 kW ASE output with a three-stage allfiberized master oscillator power amplifier structure; the central wavelength was 1074.4 nm and the FWHM line width was 8.15 nm [8]. Jin et al used a 90.9 W ASE seed ranging from 1049 nm to 1072 nm as the pumping source of a high-power, ultraflat, nearinfrared, supercontinuum source [9]. In addition to Yb-doped fibers, Tm-doped fibers can also be used to design high-power SFSs [10][11][12].…”
Section: Introductionmentioning
confidence: 99%